Pengaruh Lokasi, Variasi Produk, Harga Terhadap Keputusan Pembelian Pada Toko Bangunan Caraka Kota Metro - Rio Herdianto; Yateno; Nina Lelawati (Universitas Muhammadiyah Metro, 2025)
Consumer behavior based on current market developments makes consumers want to continue to be pampered, this encourages the creation of companies with certain models according to certain models according to consumer needs. The increasingly fierce competition in the existing market, especially competition from similar modern markets, makes companies increasingly demanded to move faster in terms of attracting consumers, so companies that apply marketing concepts need to pay close attention to consumer behavior and the factors that influence their purchasing decisions, in their marketing efforts. products carried out 1) This study aims to find out whether location has an effect on purchasing decisions 2) To find out whether product variations affect purchasing decisions. 3) To find out whether price has an effect on purchasing decisions 4) To find out whether location, product variety, price have a joint effect on purchasing decisions. The survey method was chosen as the primary data source. The survey method focuses on collecting data from respondents who have certain information, thus enabling researchers to solve problems. Data collection was carried out using a questionnaire or questionnaire instrument. In this study, the population is consumers who use telkom products. The sampling technique uses accidental sampling with a total sample of 85 people. Data collection techniques using a questionnaire with a Likert scale. The results show that 1) there is a positive and significant influence between locations on purchasing decisions. 2) there is a positive and significant influence between product variations on purchasing decisions. 3) there is a positive and significant influence between price on purchasing decisions 4) there is a positive and significant influence between location, product variations and prices there is a positive and significant influence between product variations on purchasing decisions